The Message Behind the Mural at Lembaga Pembinaan Khusus Anak DKI Jakarta - Edgar Bayu Refansyah (JSPH (Jurnal Sosiologi Pendidikan Humanis), 2024)
Mural media is one of the methods for children to express their motivation and convey theirmessages. The purpose of this research is to see how the motivation and also the sociologicalmessage conveyed by fostered children in LPKA through media murals. Previous research has atopic about messages conveyed through media murals in public spaces. In previous studies, theweaknesses found are the absence of an explanation of the specific deepening of the messageof the mural created by fostered children. This study argues that children in conflict with the lawhave the right to express their voices through any media. The theoretical approach used in thisstudy is Blumer's Symbolic Interactionism and McClelland's Achievement Motivation Theory. Thedata collection method used is participant observation and interviews with 15 children whoparticipated in the training and mural painting process at the Lembaga Pembinaan Khusus AnakKelas 2 Jakarta. The results of the activity are the findings regarding the drive for achievement,the drive to achieve power/power and the drive for affiliation by the fostered children, and theexistence of sociological messages that have special meaning from the mural works drawn byfostered children at LPKA Class 2 Jakarta.